Penerapan Model Pembelajaran Creative Problem Solving untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas VII SMP Negeri 20 Padang - YUNNEL DWESTY PUTRI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understandinggofmmathematical concepts is oneeofttheegoals of mathematics learning that musttbe managed and owned by each student. But in reality, from the results of observations and tests given, it can be seen that the student’s mathematical understanding concepts is still low. Theecontributing factors is learning that has not been fully able to facilitate students to be able to develop an understanding offmathematicallconcepts properly. Theelearninggmodel that can facilitatexstudents in understanding and constructingxtheir knowledge is the Creative Problem Solving (CPS) learninggmodel. Theepurposeeoftthis studyxis toodescribe whether understanding mathematiical concepts of students who’s learning by using the CPS learning model is better than students who learn by using the direct learning model in class VII of SMP Negeri 20 Padang. Basedoon theeresults offdataaanalysis, it wassconcluded thatuunderstanding mathematiical concepts offstudents who learn to use the CPS learning model is better thanxstudents who learn to use the direct learning model in class VII of SMP Negeri 20 Padang. Keyword – Mathematical concepts understanding, Creative Problem Solving Learning’s Model, Direct Learning